Association between duration of diabetes and fasting lipid profile in Bangladeshi type-2 diabetic patients: a series of hundred one cases - Siddiqui, Syeda Rumman Aktar; Rahman, Mohammad Zillur (International Journal Of Community Medicine And Public Health, 2025)
Background: Type 2 diabetes mellitus is a growing global health problem, with its prevalence rising significantly in developing nations. This chronic metabolic condition is characterized by persistent hyperglycemia and is strongly associated with dyslipidemia, a prime risk factor for cardiovascular diseases (CVD). The aim of this study was to evaluate the association of the length of type 2 diabetes with fasting lipid profiles of the type 2 diabetic patients. Methods: This cross-sectional descriptive type of study was carried out at the Department of Laboratory Medicine, Epic Health Care Limited, in Chattogram, Bangladesh, from December 2023 to May 2024. A total of 101 type 2 medicated diabetic cases were employed in this study. The data were analyzed using Statistical Package for Social Sciences (SPSS), Version-23.0. Results: A total of 101 type 2 medicated diabetic cases were employed in this study. The mean age of the patients was 50.11±11.87 years. The females constituted the majority 61 (60.6%). The average duration of diabetes of the participants was 8.46±6.12 years. A statistically significant association between HDL levels and the varying duration of type2 diabetes was observed (p=0.000) while the association between cholesterol, LDL, and triglycerides levels with varying duration of diabetes was not found statistically significant (P>0.05). Conclusions: This study investigated a significant association between HDL levels and the varying duration of type2 diabetes while the association between cholesterol, LDL, and triglycerides levels with varying duration of diabetes was not found statistically significant.